PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA MENGGUNAKAN MODEL PEMBELAJARAN TREFFINGER - Lisa Juanti; Budi Santoso; Cecil Hiltrimartin (Universitas Islam Negeri (UIN) Mataram, 2016)
The current research intends to clarify how Treffinger learning model improves student problem-solving skill on school mathematics subject. This research is a descriptive study. There are 30 students as the subjects and are taken from the eighth-grade students of SMPN 9 Palembang South Sumatra. The data are obtained from teaching and learning observation and student test. Based on the analysis, it is found that through Trefinger model the students whose scores are minimally 80 at the test is categorized as good skill in problem solving which is around 86.67% of students.